Ka māno wai: the source of life - Mokuau, Noreen K. (University of Hawai'i Press, 2023)
Ka māno wai is dedicated to the moʻolelo (stories) of fourteen esteemed kumu loea (expert teachers) who are knowledge keepers of cultural ways. Kamanaʻopono M. Crabbe, Linda Kaleo`okalani Paik, Eric Michael Enos, Claire Ku`uleilani Hughes, Sarah Patricia ʻIlialoha Ayat Keahi, Jonathan Kay Kamakawiwoʻole Osorio, Lynette Kaʻopuiki Paglinawan, Sharon Leinaʻala Bright, Keola Kawai`ʻla`iliahi Chan, Charles "Sonny" Kaulukukui III, Jerry Walker, Gordon "Umi" Kai, Melody Kapilialoha MacKenzie, and Kekuni Blaisdell are renowned authorities in specialty areas of cultural practice that draw from ancestral ʻike (knowledge). They are also our mentors, colleagues, friends, and family. Their stories educate us about maintaining and enhancing our well-being through ancestral cosmography and practices such as mana (spiritual, supernatural, or divine power), malama kupuna (care for elders and ancestors), ʻaina momona (fruitful land and ocean), ʻōlelo Hawaiʻi (Hawaiian language), hoʻoponopono (conflict resolution), laʻau lapaʻau (Hawaiian medicinal plants), lomilomi (massage), and lua (Hawaiian art of fighting). The trio of authors' own dedicated cultural work in the community and their deep respect for Hawaiian worldviews and storytelling created the space for the intimate, illuminating conversations with the kumu loea that serve as the foundation of the larger moʻolelo told in this book. With appreciation for the relational aspect of Native Hawaiian culture that links people, spirituality, and the environment, beautifully nuanced photographic portraits of the kumu loea were taken in places uniquely meaningful to them. The title of this book, Ka māno wai: the source of life, has multilayered meanings: In the same manner that water sustains life, ancestral practices retain history, preserve ways of being, inform identity, and provide answers for health and social justice. This collection of life stories celebrates and perpetuates kanaka values and reveals ancestral solutions to challenges confronting present and future generations. Nourishing connections to the past-as Ka Mano Wai does-helps to build a future of wellness. All who are committed to ʻike, healing, and community will find inspiration and guidance in these varied yet intertwined legacies --